The Distribution of the H‐index Among Academic Emergency Physicians in the United States. (15th October 2013) - DeLuca, Lawrence A.; John, Alex St.; Stolz, Uwe; Matheson, Lincoln; Simpson, Allan; Denninghoff, Kurt R.; Cone, David C.
Abstract Background Hirsch's h‐index (h) attempts to measure the combined academic impact and productivity of a scientist by counting the number of publications by an author, ranked in descending order by number of citations, until the paper number equals the number of citations. This approach provides a natural number or index of the number of publications and the number of citations per publication. H was first described in physics and was demonstrated to be highly predictive of continued academic activity, including recognized measures of scientific excellence such as membership in the National Academy of Sciences and being a Nobel laureate. Citation rates, research environments, and years of experience all affect h, making any comparisons appropriate only for scientists working in the same field for a similar time period. The authors are unaware of any report describing the distribution of h among academic emergency physicians (AEPs). Objectives The objective was to describe the distribution of h for AEPs and to determine whether Hirsch's demonstration of the h‐index as a predictor of continued scholarly activity among physicists would also apply to AEPs. Methods Academic EPs were identified from lists provided on allopathic U.S. emergency medicine (EM) residency program websites. "Harzing's Publish or Perish, " a free program available on the Web that queries Google Scholar, was used to calculate h for each AEP. Agreement between raters was analyzed on a subset of 100 EPs. An analysis of the 20 EPs with the top h‐indices was performed to characterize the entire body of their scholarly work, and their h‐indices were calculated at 12 and 24 years into their careers. Results A total of 4, 744 AEPs from 136 programs were evaluated. Nine programs did not publicly list the faculty at their institutions and were excluded. A linear weighted kappa was used to measure rater concordance, with agreement of 98.3% and κ = 0.92 (95% confidence interval [CI] = 0.861 to 0.957). The majority of AEPs had h‐indices of zero or one (59%), 85% had h‐indices less than six, 95% less than 13, and 99% less than 24. Ten percent of AEPs had h/(years in publication) of 0.5 or greater. For the top 20 EPs, the mean (± standard deviation [±SD]) h‐index increased from 7.6 (±4.6) to 23.5 (±9.4) between years 12 and 24. The mean (±SD) increase in h‐index was 15.8 (±7.6). Conclusions The h‐index can be used to characterize the academic productivity of AEPs. An h/year of 0.5 or greater is characteristic of the most productive EPs and represents only 10% of all AEPs. The 12‐year h‐index of top‐performing EPs was strongly related to their future academic productivity. The distribution of h among EPs may provide a means for individual investigators and academic leaders to evaluate performance and identify EPs with future success in EM research.